2006
DOI: 10.1007/s10695-006-9004-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of copper on superoxide dismutase, catalase and lipid peroxidation in the freshwater teleost fish, Esomus danricus

Abstract: Static-renewal bioassays [Methods for acute toxicity tests with fish, macro-invertebrates and amphibians: USEPA, ERS, EPA 660/3 75-009 (1975)] were carried out on Esomus danricus exposed to sub-lethal (0.55 mg/l) and lethal (5.5 mg/l) concentrations of copper. The 96-h median lethal concentration (LC 50 ) was 5.5 mg/l. Biochemical stress responses, such as visceral superoxide dismutase (SOD) and catalase (CAT) activities, were measured during this 96-h period. Malondialdehyde, a product of lipid peroxidation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 22 publications
4
56
1
Order By: Relevance
“…In the present study, substantial changes were revealed in GST and CAT activities. A decline in CAT activity at the highest copper concentration might be related to the inhibition of enzyme synthesis, or the direct binding of copper to -SH groups of this enzyme (Vutukuru et al 2006), and/or the exhaustion of its activity due to the flux of superoxide radicals (Kono and Fridovich 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, substantial changes were revealed in GST and CAT activities. A decline in CAT activity at the highest copper concentration might be related to the inhibition of enzyme synthesis, or the direct binding of copper to -SH groups of this enzyme (Vutukuru et al 2006), and/or the exhaustion of its activity due to the flux of superoxide radicals (Kono and Fridovich 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, any significant change in antioxidant levels alter peroxidation as their production above normal levels renders it non-feasible to quench the excess free radicals generated (Vutukuru et al, 2006). An increase in catalase enzyme activity at concentrations exceeding 50 μg/kg for γ-alumina, α-alumina, precipitated silica, Sb 2 O 5…”
Section: Discussionmentioning
confidence: 99%
“…The main advantages of the comet assay include: (1) the collection of data at the level of individual cells, allowing more robust statistical analyses, (2) the need for a small number of cells per sample (\10,000), (3) sensitivity for detecting DNA damage and (4) use of any eukaryotic single cell population both in vitro and in vivo (Nan et al 2013a, b). Therefore, the comet assay has been widely used for quantifying and analyzing DNA damage at the level of the individual eukaryotic cell (Vutukuru et al 2006;Topè and Rogers 2009;Li et al 2012;Azqueta and Collins 2013;Ventura et al 2013;Ganesan et al 2014). In the present study, after electrophoresis and observation by fluorescence microscopy, the damaged DNA in hepatic cells was separated from the intact DNA (the ''head'') which generated a comet ''tail'' in C. carpio (Fig.…”
Section: Resultsmentioning
confidence: 99%